Antimicrobial resistance characterization of Enterococcus faecium, Enterococcus faecalis and Enterococcus hirae isolated from marine coastal recreational waters in the State of São Paulo, Brazil - Santiago, Giovanna Silva; Dropa, Milena; Martone-Rocha, Solange; dos Santos, Talita Pereira; de Moura Gomes, Vasco Tulio; Barbosa, Mikaela Renata Funada; Razzolini, Maria Tereza Pepe (Journal of water and health, 2024)
Coastal water quality is facing increasing threats due to human activities. Their contamination by sewage discharges poses significant risks to the environment and public health. We aimed to investigate the presence of antibiotic-resistant Enterococcus in beach waters. Over a 10-month period, samples were collected from four beaches in the State of São Paulo (Brazil). Enterococcus isolates underwent matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF/MS) and molecular analysis for accurate genus and species identification. The antimicrobial susceptibility for 14 antibiotics was evaluated using the disc diffusion method followed by a multidrug-resistance (MDR) classification. PCR amplification method was used to detect antimicrobial resistance genes (ARGs). Our findings revealed the prevalence of Enterococcus faecalis, E. faecium and E. hirae. Out of 130 isolates, 118 were resistant to multiple antibiotics. The detection of resistance genes provided evidence of the potential transfer of antibiotic resistance within the environment. Our findings underscore the necessity for continuous research and surveillance to enhance understanding of the pathogenicity and antimicrobial resistance mechanisms of Enterococcus, which is crucial to implement effective measures to preserve the integrity of coastal ecosystems.